STATISTICAL ANALYSIS OF THE PRODUCTION OF BLUESTONE FROM GRANULATES (ELEMENTARY COPPER) BY OXIDATION WITH HYDROGEN PEROXIDE MIXED WITH STOCK SOLUTION OF BLUESTONE AND SULFURIC ACID - Ilić, Dragoslav (Bulletin of Natural Sciences Research, 2018)
The technological process for the production of bluestone consists of three phases: the melting of waste copper in stationary flame furnaces, the granulate dissolution with sulfuric acid in the presence of the stock solvent of copper sulphate and hydrogen peroxide, and the crystallization of copper sulphate from a saturated blue stone solution in natural baths for crystallization. This paper describes the production of bluestone using hydrogen peroxide as an oxidation agent in a mixture of sulfuric acid and a stock solution of copper sulphate as well as the statistical description and graphic representation of the dissipation of copper Cu in (%), lead Pb in (%) and nickel Ni in (%) in the production of copper sulphate. On the basis of the statistical analysis, the value of copper Cu in (%) ranged from 70.3 to 99.78%, with an arithmetic mean of 91.88800%, which shows that the value of copper only in point 4 was below 80%.